Let's go through the equation step by step and fill in the missing terms and descriptions.
Starting with the equation: \[ \frac{d+13}{16} = -1 \]
To eliminate the fraction, you can multiply both sides by 16:
- Multiply both sides by 16: \[ d + 13 = -16 \]
Next, you can simplify the equation by addressing the constant on the right side.
- The next step is subtract 13 from both sides: \[ d = -16 - 13 \] \[ d = -29 \]
So, the filled out process is:
- d + 13 / 16 = -1
- d + 13 = –16 (after multiplying both sides by 16)
- Subtract 13 from both sides
- d = -29 (after simplifying)
In summary, the completed process is:
- Missing term: -16
- Missing description: Subtract 13 from both sides
- Final answer for d: -29